Preliminary Evaluation Effect of Lepidium meyenii Walp on the embryonic development of mouse - D´Arrigo, Guadalupe (2004)
The "maca", Lepidium meyenii Walp, is a peruvian native plant and resource with a wide nutritional value. Several investigations had been realized in the last decade to probe the "maca" effects on the mammals fertility. In this work, we assessed the effects of lyophilizade aqueous extract of L. meyenii on the preimplantational embryos of Mus musculus. Two concentrations of 0 g/Kg (control group) and 1 g/Kg of body weight of lyophilizade aqueous extract were supplied to two groups of pregnant female mice, respectively from day 1 to day 4 of pregnancy. The stage of development, conditions and embryo morphology were evaluated. We found that lyophilizade aqueous extract of "maca" cause no toxics effects on the normal development of the preimplantational mouse embryos.